Informe de la Resolución N° 10 del Expediente N° 293-2016-0 - Campos Ramírez, Yrma Kassandra (Pontificia Universidad Católica del Perú, 2021)
El objetivo principal del presente informe es analizar los fundamentos esgrimidos, por la Segunda Sala Civil Superior Subespecializada en materia comercial, de la anulación de laudo parcial contenida en la Resolución N° 10 del Expediente N° 293-2016-0 referente a la afectación del principio de motivación alegada por Clothos S.L, en ese sentido, nos planteamos dos preguntas (i) ¿ Ha sido posible la revisión del laudo arbitral bajo la causal de indebida motivación por parte de los jueces de la segunda sala civil subespecializada en materia comercial sin la necesidad de ver el fondo de la controversia? y (ii) ¿ Qué otras patologías encontramos en la Resolución N° 10 del Expediente N°293-2016-0? que hemos desarrollado en el presente informe. Para ello, ha sido necesario determinar en qué consiste el recurso de anulación de laudo, como este está regulado en nuestra legislación peruana, ante que casos es posible su interposición y ante qué supuesto de afectación a la motivación es posible el pronunciamiento por los jueces. Además, ha sido de igual relevancia determinar el contenido del principio de congruencia y su aplicación en las resoluciones judiciales. En ese sentido, se concluyo que la Sala sí se pronunció respecto a la motivación dada por el Tribunal Arbitral; además, vulneró el principio de congruencia al no pronunciarse en tres de 4 fundamentos manifestados por Clothos S.L en su demanda.

The main objective of the present report is to analyze the grounds given by the Second Superior Civil Sub Specialized Chamber in commercial matters, for the annulment of the partial award contained in Resolution No. 10 of File No. 293-2016-0 regarding the violation of the principle of motivation alleged by Clothos S. L., in this sense, we raise two questions (i) Has it been possible to review the arbitral award under the grounds of improper motivation by the judges of the Second Civil Sub Specialized Chamber in commercial matters? L, in that sense, we raise two questions (i) Has it been possible the review of the arbitration award under the cause of undue motivation by the judges of the second civil sub-specialized chamber in commercial matters without the need to see the merits of the controversy? and (ii) What other pathologies we found in Resolution No. 10 of File N°293-2016-0? which we have developed in this report. For this purpose, it has been necessary to determine what the appeal for annulment of the award consists of, how it is regulated in our Peruvian legislation, before which cases it is possible to file it and before which cases of affectation of the reasoning it is possible to be pronounced by the judges. In addition, it has been of equal relevance to determine the content of the principle of congruence and its application in judicial resolutions. In this sense, it was concluded that the Chamber did pronounce on the reasoning given by the Arbitral Tribunal; moreover, it violated the principle of congruence by not pronouncing on three of the four grounds stated by Clothos S.L. in its claim.
Keywords: Arbitraje--Legislación--Perú; Arbitraje y laudo; http://purl.org/pe-repo/ocde/ford#5.05.01